Dinamika Ruang Berbasis Gender, Kelayakan Huni, dan Keberlanjutan dalam Transformasi Arsitektur Tradisional Bali - Risky Handayani; Erza Rahma Hajaty; Azka Pintra; Rizki Hambali (Jurnal Arsitektur ARCADE, 2026)
Abstract: The development of tourism in Bali has transformed traditional houses, courtyards, and ritual spaces into environments that serve not only domestic life but also economic activities. Houses and courtyards are now utilized as homestays, culinary production areas, tourism service facilities, and venues for cultural activities. Many studies have interpreted these transformations as manifestations of cultural and economic sustainability. However, discussions concerning gendered spatial dynamics and their implications for habitability remain limited. This article synthesizes the literature on the relationships among gendered space, habitability, and sustainability in the transformation of traditional Balinese architecture. The study employs a Systematic Literature Review (SLR) of 20 national and international journal articles. The selected literature was analyzed thematically to examine the interconnections between spatial transformation, gender-based division of labor, habitability, and sustainability. The findings indicate that the sustainability of Bali’s tourism sector is substantially supported by women’s labor within domestic and ritual spaces. While these roles contribute to the preservation of cultural practices and the strengthening of household economies, they may also reinforce gendered spatial divisions and reduce the quality of women’s lived experiences within the home environment. This article argues that the sustainability of traditional Balinese architecture should not be assessed solely through building preservation, cultural continuity, or economic growth. The experiences of women as primary users of productive domestic spaces must also be recognized as a critical component in evaluating habitability and the broader sustainability of the built environment. Keyword: gendered space, habitability, sustainability, traditional Balinese architecture, tourism Abstrak: Perkembangan pariwisata di Bali mengubah rumah tradisional, pekarangan, dan ruang ritual menjadi ruang yang tidak hanya melayani kehidupan domestik, tetapi juga kegiatan ekonomi. Rumah dan pekarangan kini digunakan sebagai homestay, tempat produksi kuliner, ruang pelayanan wisata, dan bagian dari aktivitas budaya. Banyak kajian membaca perubahan ini sebagai bentuk keberlanjutan budaya dan ekonomi. Namun, pembahasan tentang dinamika ruang berbasis gender dan dampaknya terhadap kelayakan huni masih terbatas. Artikel ini menyintesis literatur tentang hubungan gendered space, kelayakan huni, dan keberlanjutan dalam transformasi arsitektur tradisional Bali. Metode yang digunakan adalah Systematic Literature Review terhadap 20 jurnal nasional dan internasional. Literatur dianalisis secara tematik untuk melihat hubungan antara perubahan ruang, pembagian kerja berbasis gender, kelayakan huni, dan keberlanjutan. Hasil kajian menunjukkan bahwa keberlanjutan pariwisata Bali banyak ditopang oleh kerja perempuan di ruang domestik dan ritual. Peran ini menjaga budaya dan mendukung ekonomi keluarga, tetapi juga berpotensi memperkuat pembagian ruang berbasis gender serta menekan kualitas pengalaman huni perempuan. Artikel ini menegaskan bahwa keberlanjutan arsitektur tradisional Bali tidak cukup dinilai dari bentuk bangunan, pelestarian budaya, dan pertumbuhan ekonomi. Pengalaman perempuan sebagai pengguna utama ruang domestik produktif perlu menjadi bagian penting dalam penilaian kelayakan huni. Kata Kunci:  ruang berbasis gender, kelayakan huni, keberlanjutan, arsitektur tradisional Bali, pariwisata